Urgensitas Komunikasi Antarbudaya dalam Menjalin Hubungan Inklusif Masyarakat di Kota Mataram - Hazani, Dewi Chandra (YASIN, 2023)
This inclusive relationship between religious adherents in the City of Mataram, West Nusa Tenggara must continue to be built so that people always get along harmoniously in the diversity of cultures and religions they adhere to. The purpose of this study is to find out how important intercultural communication must be built in the cultural and religious diversity that exists in the city of Mataram. This type of descriptive qualitative research uses a phenomenological approach, namely trying to understand the meaning of a human event through interviews. The data sources in this study are primary data sources and secondary data sources. Collection methods are observation, interviews and documentation. The results of this study indicate that the importance of intercultural communication in urban life is to create inclusive relationships between religious adherents in the city of Mataram whose population is balanced between Hindus, Muslims and Christians based on openness and mutually associative processes both celebrating holidays such as Nyepi, Christmas, Eid, Eid al-Adha and Weddings. In social interaction, the community uses primary communication to create harmony in society and uses linear communication which tends to use persuasive communication in changing people's attitudes and behavior as expected by religious leaders, community leaders, government and all stakeholders and stakeholders. The implication of this research is the importance of communication that must continue to be built in inclusive relationships between religious adherents in the city of Mataram, which used to be a step event, now it tends to be easy to fulfill due to communication, awareness and willingness of the community to build fraternal relations characterized by primary communication. and linear. In other words, the two models of communication tend to be humanist which is an investment or provision in creating interfaith brotherhood relations. Therefore, it is hoped that the city government, religious leaders and all stakeholders will continue to maintain inclusive and peaceful relations between religious communities.